A phase I/II trial of vorinostat (SAHA) in combination with rituximab‐CHOP in patients with newly diagnosed advanced stage diffuse large B‐cell lymphoma (DLBCL): SWOG S0806. Issue 4 (25th January 2018) - Persky, Daniel O.; Li, Hongli; Rimsza, Lisa M.; Barr, Paul M.; Popplewell, Leslie L.; Bane, Charles L.; Von Gehr, Ann; LeBlanc, Michael; Fisher, Richard I.; Smith, Sonali M.; Friedberg, Jonathan W.
Abstract: Loss of major histocompatibility Class II expression (MHCII) in diffuse large B‐cell lymphoma (DLBCL) correlates with decreased survival. MHCII transcription is in part regulated by histone acetylation. We tested the hypothesis that combination of histone deacetylase inhibitor (HDACI) with standard chemotherapy would improve outcomes in DLBCL in part through increased MHCII expression. S0806 was a single arm phase I/II trial of vorinostat given at 400 mg po daily on days 1‐9 (subsequently amended to days 1‐5 due to toxicity), combined with R‐CHOP given on day 3 of a 21‐day cycle for 8 cycles, with primary phase II endpoint of 2‐year progression free survival (PFS). With 72 evaluable patients, at median follow up of 3 years, 2‐year PFS estimate was 73%, and OS estimate was 86%. Considering that the regimen fell short of predefined efficacy improvement and was associated with high rates of febrile neutropenia (38%) and sepsis (19%), it cannot be recommended for general use. Consistent with our hypothesis, patients with low MCHII expression on S0806 had numerically superior outcomes compared to those from trial S0433 which did not use an HDACI, but the difference was not statistically significant. Current studies are focused on finding biomarkers of response to HDACI.